Evoluç\~ao das cadeias produtivas brasileiras na década de 90 - Lia Haguenauer; Luiz Dias Bahia; Paulo A. Castro; Márcio Bruno Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– This paper analyses the evolution of the Brazilian manufacturing sector from 1990 to 1999, using inter-sector relations derived from input-output matrixes and production indexes. The main conclusion is that a narrowing of intermediate relations took place on several productive supply chains, in spite of the relative stability of the manufacturing sector structure as a whole. The paper finds also that the most competitive sectors were the same before and after the trade liberalization and were the ones which process raw materials.
Keywords: 330